CRIMINAL JUSTICE SYSTEM POLICY ON CYBER CRIME: CAUSES AND PREVENTIVE MEASURES - Kumar, Mahendra; Grewal, Upendra (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The emergence of cybercrime due to the development of computer technologies has become a significant issue in recent years. Cyber-crime mainly involves activities that use internet and computers as a tool to extract private information of an individual either directly or indirectly and disclosing it on online platforms without the person’s consent or illegally with the aim of degrading the reputation or causing mental or physical harm. The recent shift in criminal activities includes organized crime, white-collar crime, and cybercrime. The increased use and access to digital space have influenced the prevalence of cyber-criminal behavior over time. Therefore, using electronic equipment to get access to prohibited or unlawful information is one sort of criminal cyber activity. The research examines the evolving policies within the criminal justice system aimed at addressing cyber-crime, focusing on underlying causes such as anonymity, technological vulnerabilities, and socioeconomic factors, while proposing preventive measures like enhanced legislation, international cooperation, and public awareness campaigns. Drawing from recent developments, including the 2024 UN Cybercrime Convention and 2025 U.S. state cyber security legislation, the paper highlights gaps in current frameworks and recommends integrated strategies to mitigate risks. Additionally, it explores the inadequacies of existing laws and the necessity for legislative reforms to adapt to the digital age effectively.